2017
DOI: 10.1038/ncomms14794
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the hidden link of lithium halides and application in the synthesis of organocuprates

Abstract: As a versatile metal, copper has demonstrated a wide application in acting as both organometallic reagent and catalyst. Organocuprates are among the most used organometallic reagents in the formation of new carbon–carbon bonds in organic synthesis. Therefore, revealing the real structures of organocuprates in solution is crucial to provide insights into the reactivity of organocuprates. Here we provide several important insights into organocuprate chemistry. The main finding contains the following aspects. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Based on previous researches in X-ray absorption fine structure (XAFS), we found that the equilibrium between organocuprates and radicals could serve as persistent radical [20][21][22]. This reveals that transient radical could be translated into persistent radical in special conditions.…”
Section: The Concept Of ''Tuning Radical Reactivitymentioning
confidence: 80%
“…Based on previous researches in X-ray absorption fine structure (XAFS), we found that the equilibrium between organocuprates and radicals could serve as persistent radical [20][21][22]. This reveals that transient radical could be translated into persistent radical in special conditions.…”
Section: The Concept Of ''Tuning Radical Reactivitymentioning
confidence: 80%
“…Visible light photoredox catalysis has emerged as a powerful technique in organic synthesis in recent years, providing a mild condition for organic transformation. In continuation of our interest in the development of C–H activation/functionalization methods and mechanistic studies, seeking a mild and green way is always under operation in our lab. Herein, we report a simple and mild metal-free catalytic oxidative amination approach via α-C­(sp 3 )-H activation of tetrahydrofuran mediated by visible-light using air as benign oxidant (Scheme ).…”
mentioning
confidence: 99%
“…In addition, disulfiram’s covalently bonded skeleton made of C, N, S and non-acidic protons is less likely to destroy the main phase compared to reagents made of halogens, nitronium or acidic protons. We also tried to dissolve Cu + cations at Step 1 as organolithium cuprates 26 before they are reduced to elemental Cu 0 but these attempts were so far unsuccessful. Nevertheless, the one-pot removal of Cu would significantly simplify the synthetic procedure and therefore this will be one of our next challenges in synthetic methodology.…”
Section: Resultsmentioning
confidence: 99%